Blackface, white noise : Jewish immigrants in the Hollywood melting pot - Rogin, Michael Paul (University of California Press, 1996)
The founding Hollywood movie, Birth of a Nation, celebrated the Ku Klux Klan. The first talking picture, The Jazz Singer, was a blackface film. Gone With the Wind remains the all-time box-office success. From their beginnings, Michael Rogin claims, motion pictures created a national culture by taking possession of African Americans. Blackface, White Noise investigates Hollywood's roots in the most popular original form of American mass culture, blackface minstrelsy. Through its use in films from Uncle Tom's Cabin and Birth of a Nation to Forrest Gump, motion picture blackface becomes an aperture opening onto major issues of American national identity: the meanings of whiteness, the role race has played in turning settlers and immigrants into Americans, and the tangled connections that have bound Jews to African Americans in popular culture and liberal politics.